A Clinicopathologic Analysis of Decidual Polyps: A Potentially Problematic Diagnosis. (11th April 2022) - Zou, Juan; He, Ying; Chen, Huiling; Wang, Peng; Xiao, Xue; Liu, Shanling
Abstract : Objective . The decidual polyp is a special cervical polyp that is not systemically reported or well known. The aim of this study was to describe the clinicopathologic features of the decidual polyps observed at the West China Second University Hospital of Sichuan University between 2015 and 2020 and to spread awareness of them. Methods . Two hundred and fifty cases of decidual polyps, accounting for 45.45% (250/550) of all cervical polyps identified during pregnancy, were reviewed. The patients were followed up until the end of their pregnancies, which delivered <28 weeks and between 28 and 37 weeks, and full-term delivery. The t -test or nonparametric test was used to measure the data, and the chi-square test was used for counting data. Statistical significance was set at p < 0.05 . Results . Most of the decidual polyps occurred during the first trimester, with a median patient age of 33 years. The polyps were both singles and multiples and located at the cervix, with a long stalk, and a median diameter of one centimeter. The gross morphological appearance varied from polypoid to lingulate, and they were fragile and bled easily. Microscopically, the decidual polyps showed diffuse glandular secretion as well as decidual changes in the stromal cells. They could be divided into two subtypes: decidua fragment and decidua with endometrial polyp formation. Seventy-three patients who went on to have further pregnancies were followed until the end of the study period. Twenty-one (21/73, 28.77%) of them had adverse pregnancy outcomes (12 cases delivered <28 weeks and 9 cases delivered between 28 and 37 weeks). Conclusions . The data showed that the decidual polyp was the second most common cervical polyp during pregnancy, and its incidence was associated with adverse pregnancy outcomes. Thus, this type of polyp should be considered in cervical polypectomy specimens from pregnant women. A more uniform and accurate pathological diagnosis, including the thrombus status and division subtype, could provide the basis for obstetricians to promote treatment improving pregnancy outcomes.